2023
DOI: 10.1021/acsomega.3c08460
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability in Rheumatoid Arthritis: A Bibliometric Analysis and Retrospective Data Mining Study

Fanfan Wang,
Jian Liu,
Yanyan Fang
et al.

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic systemic inflammation, leading to joint deformities and functional loss. RA progression is accompanied by abnormalities in the coagulation–fibrinolysis system, clinically manifested as a hypercoagulable state. However, there are currently no bibliometrics or visualization analysis in this field. Objective: The present study aims to reveal the knowledge structure, research status, and research trends related to hypercoagulab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Inflammatory activity triggers the formation of a hypercoagulable state with concomitant changes in D-dimer [ 25 ]. Several investigators have confirmed the correlation between D-dimer levels and rheumatoid arthritis activity indices through retrospective data mining [ 26 ]. In addition to its predictive value for the diagnosis of VTE in CTD patients [ 27 ], it has been shown that D-dimer level is also a valid serologic index for assessing disease activity in some CTD patients [ 28 , 29 ].…”
Section: Vte Associated With the Systemic Inflammatory Responsementioning
confidence: 99%
“…Inflammatory activity triggers the formation of a hypercoagulable state with concomitant changes in D-dimer [ 25 ]. Several investigators have confirmed the correlation between D-dimer levels and rheumatoid arthritis activity indices through retrospective data mining [ 26 ]. In addition to its predictive value for the diagnosis of VTE in CTD patients [ 27 ], it has been shown that D-dimer level is also a valid serologic index for assessing disease activity in some CTD patients [ 28 , 29 ].…”
Section: Vte Associated With the Systemic Inflammatory Responsementioning
confidence: 99%
“…Bibliometrics is an emerging overview analysis, which can systematically analyze topics regarding research trends, status, and hotspots . More importantly, bibliometrics can handle a large amount of literature data . With the help of literature visualization tools, existing research gaps can be identified, and emerging research ideas can be revealed more rigorously .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] One important factor contributing to the health burden of RDs on patients and healthcare systems is represented by a state of hypercoagulability with a predisposition to venous thromboembolism (VTE). 17,18 This issue has been well studied in specific RDs, for example, RA (increased risk of VTE by a factor of 2−2.5 vs. general population), [19][20][21] systemic lupus erythematosus (SLE, increased risk of VTE by a factor of 4.38 vs. general population), 22,23 systemic sclerosis (SSc) (increased risk of VTE by a factor of 2.5 vs. general population), 24 ANCA-associated vasculitis (AAV) (increased risk of VTE by a factor of 3.26 vs. general population), [25][26][27][28][29][30][31] CA and gout (increased risk of VTE by a factor of 1.33 vs. general population), 32 osteoarthritis (OA) (increased risk of VTE by a factor of 1.38 vs. general population), 33 and Behcet disease (BD) (increased risk of VTE by a factor of 2.80 vs. general population). [34][35][36][37] It is commonly accepted that the proinflammatory and pro-oxidant state in patients with RA and SLE favors the upregulation of procoagulant pathways and the downregulation of anticoagulant and fibrinolytic pathways.…”
Section: Introductionmentioning
confidence: 99%